PENGGUNAAN APLIKASI GEOGEBRA TERHADAP MOTIVASI BELAJAR SISWA DI MTs BABUL ULUM KELAS VIII - Suriyana; Ika Sari Fitriyana; Mita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the level of students’ motivation in learning mathematics after implementing the GeoGebra application in teaching solid geometry. The background of this study is the low motivation among students due to the abstract nature of mathematics, especially in topics like three-dimensional geometry, which are often difficult to visualize and understand. This research uses a quantitative descriptive method. The population consisted of 12 eighth-grade students at MTs Babul Ulum. Data collection techniques included student motivation questionnaires and classroom observation sheets. Data were analyzed using descriptive statistics based on a Likert scale. The results showed that the implementation of learning using GeoGebra was categorized as very good, with an average score of 90%. Students’ learning motivation was also in the 'good' category, with an average score of 78.83. The use of GeoGebra significantly enhanced students’ engagement and interest in learning and helped make abstract mathematical concepts more visual, concrete, and enjoyable.